Sensitivity Analysis in Decision Making. - Rappaport, Alfred (The Accounting Review, 1967)
This article focuses on a study which illustrated how sensitivity analysis can serve as an aid in improving the basis for management decision making. Freedom from uncertainty is a luxury rarely enjoyed by the contemporary manager. In a society characterized by change, uncertainty is an established and accepted fact of life. Sensitivity analysis is a study to determine how possible changes or errors in parameter values affect model outputs. The prime function of sensitivity analysis may be said to be to facilitate a better understanding of risk. Specifically, sensitivity analysis tests the responsiveness of model results to possible variations in parameter values, and thereby offers valuable information for appraising the relative risk among alternative courses of action. Implicitly or explicitly, managers have actively employed sensitivity tests for appraising relative risk of alternative courses of action from the earliest stages of business development.